Lost in transition : removing, resettling, and renewing Appalachia - Purcell, Aaron D., 1972- (The University of Tennessee Press, 2021)
"Volume editor Aaron D. Purcell presents this thematic and chronological exploration of twentieth-century removal and resettlement projects across southern Appalachia. The work's seven case studies, addressing public land removal actions in Virginia, Kentucky, the Carolinas, and Tennessee from the 1930s through the 1960s, reveal confrontations between past and present, federal agencies and citizens, and original accounts and contemporary interpretations. The result is a critical analysis of fact, mythology, and storytelling that illustrates the important role of place in southern Appalachian history"-- Provided by publisher.
Keywords: Appalachians (People) -- Relocation -- History -- 20th century.; Appalachians (People) -- Relocation -- Case studies.; Appalachians (People) -- Ethnic identity.; Persons displaced by eminent domain -- Appalachian Region, Southern -- Case studies.; Public lands -- Appalachian Region, Southern -- 20th century.; Public lands -- Social aspects -- Appalachian Region, Southern.; Terres publiques -- Appalaches (Sud) -- 20e siècle.; Terres publiques -- Aspect social -- Appalaches (Sud); Appalachians (People) -- Ethnic identity; Persons displaced by eminent domain; Public lands; Southern Appalachian Region; HISTORY / United States / 20th Century; 1900-1999; Case studies; History